Data Acquisition System Prototype of the ITER Diagnostic Divertor Neutron Flux Monitor Testing at Research Nuclear Facilities - Martazov E.S. (EDP Sciences, 2021)
The Divertor nuclear flux monitor (DNFM) is one of the ITER neutron diagnostics. This diagnostic consists of the three same subsystems. Each subsystem concludes the detector module with fission chambers (FCs) and the data acquisition system (DAQ). To solve the task of the neutron flux measurements in the range of 7 orders of magnitude and 1 ms of time resolution the multidetector module is used. To confirm the possibility of the neutron flux measurements in a wide range using such a detector module and to evaluate the characteristics of the DAQ prototype a number of tests were carried out under conditions of the intense neutron radiation. The detector module and the DAQ, which are the prototype of the equipment planned for use on site were used for the tests. The tests were carried out at the plasma neutron diagnostic stand based on the NG-24M neutron generator and at the IBR-2 pulsed reactor of the Joint Institute for Nuclear Research. During the tests at the plasma neutron diagnostic stand the data for the calibration of the DNFM DAQ measuring channels were collected. During the tests at the IBR-2 pulsed reactor the signals from the measuring channels of the DNFM subsystem were obtained while the neutron flux was changed. This report shows the test results and the subsystem calibration techniques.